PEMBERDAYAAN PONDOK PESANTREN & PANTI ASUHAN AL-MUKMIN DI PONJONG GUNUNG KIDUL - Endah Wahyurini; Hendro Widjanarko (Dharma: Jurnal Pengabdian Masyarakat, 2020)
Pondok Pesantrean & Orphanage of Al-Mukmin Ponjong Gunung Kidul has problems in entrepreneurship learning for cottage children. Community service is aimed at providing skills to the orphanage children as well as increasing the orphanage's income. The activities carried out are planting herbal plants in critical land, herbal production, and marketing herbal products. The methods implemented are training, provision of agricultural and production facilities, production and marketing assistance. The results that are felt are the increased knowledge and skills of the orphanage in managing the business as well as cottage income to finance learning activities.